Assessment of Hematological changes in Chronic Kidney Failure patients undergoing Hemodialysis - Sajid Hussain Askary, Syeda Samira Azim, Bushra Anwar, Syed Munawar Alam, Rafia Siddiqui, Syeda Asiya Parveen (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Chronic kidney failure leads to a gradual loss of kidney function, necessitating interventions like hemodialysis, which significantly impacts patients’ hematological profiles. Understanding these hematological changes is crucial for improving patient management and outcomes, especially in specific populations like those in Pakistan. Objectives: To investigate the hematological changes in chronic kidney failure patients undergoing hemodialysis. Methods: This cross-sectional study was conducted at Department of Pathology Fazaia Medical College Air University, Islamabad from 3rd May 2023 to 27th October 2023. The adult patients ≥18 years diagnosed with chronic kidney failure (CKD Stage 5) and undergoing maintenance hemodialysis for at least three months were included. Blood samples were collected from participants before the hemodialysis session, ensuring they were in a fasting state for at least 8 hours. These parameters were assessed using automated hematology analyzers and standard biochemical assays in the hospital’s central laboratory. Results: There were 55 (61.1%) males and 35 (38.9%) females in CKF patients whereas in control 54 (60%) and 36 (40%) females respectively. The mean age of CKF patients was 45.38±14.35 years, while that of controls was 44.01±12.30 years Among CKF patients, hypertension 24 (26.7%), diabetes mellitus 20 (22.2%), and the combination of diabetes mellitus with hypertension 30 (33.3%) were the predominant causes of renal failure necessitating hemodialysis. The distribution of CKF patients based on the severity of anemia revealed that a substantial proportion suffered from moderate anemia 42 (46.7%), followed by mild anemia 34 (37.8%). Few CKF patients exhibited severe anemia 6 (6.7%), while 8 (8.9%) showed normal hemoglobin levels. Conclusion: The significant hematological abnormalities in chronic kidney failure patients undergoing hemodialysis in Pakistan, including lower levels of red blood cells, hemoglobin, and platelets compared to healthy controls Keywords: Anemia, Chronic kidney disease, Hematological changes, Hemodialysis, Leukopenia, Thrombocytopenia